Late Neandertals in central Italy. High-resolution chronicles from Grotta dei Santi (Monte Argentario - Tuscany). (1st August 2019) - Moroni, Adriana; Boschian, Giovanni; Crezzini, Jacopo; Montanari-Canini, Guido; Marciani, Giulia; Capecchi, Giulia; Arrighi, Simona; Aureli, Daniele; Berto, Claudio; Freguglia, Margherita; Araujo, Astolfo; Scaramucci, Sem; et al.
Abstract: Most of the Middle Palaeolithic evidence of Central Italy still lacks a reliable chrono-cultural framework mainly due to research history. In this context Grotta dei Santi, a wide cave located on Monte Argentario, on the southern coast of Tuscany, is particularly relevant as it contains a very well preserved sequence including several Mousterian layers. Research carried out at this site in the last years (2007–2017) allowed for a preliminary estimation of its chronology based on a set of radiometric determinations which place the investigated sequence in the time interval between 50 and 40 ka BP. Alongside the chronological issue, this paper mainly focuses on the geoarchaeological and zooarchaeological (micro and macro fauna) studies carried out on the materials retrieved during the 2007–2014 excavation fieldworks. The results of these studies are consistent with those from the radiometric chronology. A state of art concerning the MIS3 Italian sites is also provided in order to highlight the key role Grotta dei Santi may play in the assessment of late Neandertals' behaviour within the framework of the Middle to Upper Palaeolithic transition of Central Italy. Highlights: Key Mousterian deposit not excavated before due to difficult accessibility. The deposit has been radiometrically dated to 50-40ka BP. Recurrent short-lasting occupations with largely undisturbed living floors. New chrono-cultural and palaeoenvironmental data on late Neandertals in Central Italy.